Evidence-Based Genetic Education of Non-Genetic-Expert Physicians: Experiences Over Three Decades in Amsterdam - Cornel, Martina C. (Frontiers in Genetics, 2019)
To study and improve the competences of health care workers in the domain of genetics, attention needs to be paid to attitudes, activities, knowledge and changes in performance. Three decades of research on genetic education for non-genetic-experts in Amsterdam is summarized, including both local and international collaborative efforts. Evidence shows that assessment of learners’ needs, and the definition of competences has driven slow but gradual improvement in genetics competence among non-geneticists. Attitudes and behavior are mainly influenced by face-to-face training. eLearning modules can serve to increase knowledge in a large number of participants in a rapidly changing field. Materials developed for accredited courses will sometimes be used for reference or just in time learning. Taking a theoretically informed evaluation approach, it has been possible to demonstrate satisfaction, improved knowledge and self-reported behavioral change, although measuring effects on health care practice and population health remains challenging. A flexible approach is needed to serve learners’ needs in a field with many upcoming challenges.